Do HIV/HCV co-infected patients need haematopoietic growth factors earlier than non-co-infected during HCV treatment?. Issue 2 (12th March 2012) - Urbina, O.; Ferrández, O.; Luque, S.; Espona, M.; Florit, M.; Pellicer, R.; Carmona, A.
Abstract : Background: Hepatitis C treatment (HCVt) with peg-interferon and ribavirin is limited by haematological side-effects. Haematopoietic growth factors (HGF) allow to maintain standard antiviral doses in order to achieve sustained virological response in hepatitis C (HCV) infected patients. Purpose: To evaluate if HIV/HCV co-infected patients need HGF earlier than non-coinfected during HCVt. Clinical and haematological characteristics of HCV-infected-patients receiving HGF were compared between HIV+ vs HIV-. Materials and methods: Retrospective study in a third level hospital including all patients on HCVt that needed HGF between January 2008 and February 2011. Data: HIV-co-infection, age, gender, HCV-genotype, HCVt, haematological parameters, HGF. Statistical analyses: χ 2 and Fischer exact test for dichotomic variables and t-student and 'U' Mann-Whitney tests for continuous variables. Results: 132 patients. 33(25%) HIV+. Characteristics HIV ± versus HIV-: ▶ Age: 50.3± 7.6 versus 52± 11.1 p=0.412 ▶ Male: 26(78.8%) versus 58(58.6%) p=0.039 ▶ Genotype(G): G1: 17(51.5%) versus 66(66.7%), G2: 2(6.1%) versus 2(2%), G3: 10(30.3%) versus 18(18.2%), G4: 4(12.1%) versus 10(10.1%), non-typeable: 0(0%) versus 3(3%). ▶ All patients received ribavirin. All HIV+ received peg-interferon α2a. HIV- received 88(88.9%) peg-interferon α2a and 11(11.1%) peg-interferon α2b. Patients on HGF (HIV± vs HIV-). Erythropoietin: 26(78.8%) versus 78(78.8%). Filgrastim: 15(45.5%) versus 33(33.3%). Both: 8(24.2%) versus 12(12.1%). Days until erythropoietin initiation 76(32-124) versus 103(57-192) (p= 0.15). Days until filgrastim initiation 92(58-124) versus 97(48-224) (p= 0.72) Conclusions: HIV/HCV co-infected patients did not initiate HGF earlier than non-co-infected, although a tendency to a shorter period of time until starting erythropoietin was observed. A greater percentage of HIV+ seemed to need the use of both, erythropoietin and filgrastim, although it was not significant. Haematological parameters at the beginning of HCVt and HGF were similar in both groups.